Magnetic properties of siliceous marine sediments in Northern Hokkaido, Japan: a quantitative tectono‐sedimentological study of basins along an active margin. (25th May 2013) - Itoh, Y.; Kusumoto, S.; Inoue, T.
Abstract The formation processes of the late Neogene sedimentary basins in Northern Hokkaido have been investigated on the basis of rock magnetism, structural geology and numerical modelling. Untilted site‐mean directions of remanent magnetization of the Wakkanai Formation, obtained from oriented core samples in Horonobe, suggest remarkable counterclockwise block rotation (ca. 70°) since the late Neogene. Uniform microscopic fabric of the siliceous sediments was inferred from the alignment of the principal axes of the anisotropy of magnetic susceptibility (AMS). After correction for tectonic rotation, the maximum axis of AMS, which reflects the sedimentary fabric of the dominant paramagnetic minerals, is in an E‐W direction, which is concordant with the influx direction of diatomaceous particles into the N‐S elongate sedimentary basins. The difference in the bulk initial magnetic susceptibility of the siliceous sediments of the Wakkanai Formation between the depocenter of the basin and its peripheral part implies that terrigenous non‐magnetic fraction has been sorted out during transportation of the detrital grains as gravity flows. As for the development mechanism of the N‐S elongate late Neogene basins in Northern Hokkaido, their depocenter arrangement and subsidence pattern indicates dextral motions upon a longitudinal fault zone along the Eurasian convergent margin. Dislocation modelling was adopted to explain vertical displacement and rotational motion around the study area and successfully restored the deformation pattern based on the assumption of dextral slip at a left‐stepping part of a strand of the transcurrent fault.